Mycobacterium tuberculosis concealed by enterococcal sacroiliitis. (2020) - Chandradevan, Raguraj; Takeda, Hironobu; Lim, Tanna; Patel, Nidhip
Abstract: A 77-year-old African American female with rheumatoid arthritis presented with fever and unsteady gait. She was started on broad-spectrum antimicrobials due to CT evidence for sacroiliitis and psoas abscess and underwent partial excision of her sacroiliac bone and drainage of the abscess. One of four blood cultures grew Enterococcus faecalis and the patient was sent home with intravenous ampicillin for 6 weeks. Two days after antimicrobial completion, the patient presented with night sweats and weakness. Chest x-ray revealed new right upper lobe pulmonary infiltrates, and the AFB culture sent during her prior admission returned positive for TB. RIPE therapy with moxifloxacin was initiated. Although she responded well to treatment, she retained functional immobility. We report a case of musculoskeletal TB initially misdiagnosed as enterococcus sacroiliitis, resulting in a delayed initiation of anti-tuberculous therapy. A high index of suspicion and rapid detection with TB-PCR testing should be considered to avoid delayed diagnosis.